David N. Lorenzen, El flagelo de la Misión: Marco della Tomba en Indostán, México, El Colegio de México, 2010, 223 pp. - Martha Elena Vernier (El Colegio de México, A.C., 2011)
David N. Lorenzen, El flagelo de la Misión: Marco della Tomba en Indostán, México, El Colegio de México, 2010, 223 pp.